Republished: Emerging concepts in the management of acute retinal necrosis. Issue 1054 (16th July 2013) - Wong, Robert William; Jumper, J Michael; McDonald, H Richard; Johnson, Robert N; Fu, Arthur; Lujan, Brandon J; Cunningham, Emmett T
Abstract : Acute retinal necrosis (ARN), also known as Kirisawa-type uveitis, is an uncommon condition caused by infection of the retina by one of the herpes family of viruses, most typically varicella zoster virus or herpes simplex virus and less commonly cytomegalovirus. Clinical diagnosis can be challenging and is often aided by PCR-based analysis of ocular fluids. Treatment typically involves extended use of one or more antiviral agents. Long term retinal detachment risk is high. We review the literature on ARN and present an approach to the diagnosis and management of this serious condition.